Finite element analysis of prestressed pretension concrete T-Beam - Ishag Adam, Elwalid Adam (2013)
Prestressed concrete constructions become a one of the famous constructions method. The stresses occurred in concrete and reinforcement became kind of complex due to prestressing and applying loads. And in reasons of costs and time for lab tests, Three-dimensional nonlinear finite element model of prestressed reinforced concrete T-beam had been developed in this study. This lead to the requirement by codes of practice to obtain design parameters for each new system by extensive fullscale testing. According to the high costs and time consuming for laboratory tests. Many researchers tried to propose alternative methods of small-scale testing and finite element models. These methods are still being refined to make them more accurate and practical for use in design offices. In this study we are going to develop a model to simulate a model had been tested at lab of structure in Universiti Teknologi Malaysia and to obtain the best method of modeling the specimen. At the end of this study it should be aim to develop a 3D finite element model of prestressed concrete T-beams and analyzed them using finite element software, ANSYS package. Interface elements will be used for modeling bond interaction between concrete, reinforcement and prestressed force in tendons. And by applying loads up to ultimate loads and plot the graph of loads verses displacement in linearity region, and by increasing loads up to non-linearity region will be illustrated in the criteria of flexure behavior. The results was be verified against published experimental data for test on T-beam done in Universiti Teknologi Malaysia. It is expected that, by using the mentioned combination, a more accurate model was be achieved as compared to result out from tests.